Difference in implant design affects midflexion rotational laxity in cruciate‐retaining total knee arthroplasty: a computer navigation study - Takashi Tsuda; Kazunori Hino; Tatsuhiko Kutsuna; Kunihiko Watamori; Tomofumi Kinoshita; Masaki Takao (Journal of Experimental Orthopaedics, 2023)
Abstract Purpose This study aimed to compare midflexion rotational laxity between two different design concept models of cruciate‐retaining total knee arthroplasty: symmetrical surface design of neutral joint line obliquity and asymmetrical surface design of varus joint line obliquity. Methods Sixty‐three knees that underwent cruciate‐retaining total knee arthroplasty were evaluated. Manual maximum passive rotational stress without acceleration was applied to the knees under navigation monitoring. Pre‐operative and post‐operative internal and external rotational angles were measured at 30°, 45°, 60°, and 90° knee flexion. Results The post‐operative internal rotational laxity was significantly increased compared with pre‐operative levels at 30°, 45°, 60°, and 90° flexion among all subjects (mean 9.7° vs 11.1°, 10.6° vs 11.6°, 11.2° vs 12.9°, and 13.2° vs 14.9°; p = 0.01, 0.04, 0.001, and 0.008, respectively). The post‐operative external rotational laxity was significantly decreased compared to pre‐operative levels at 30°, 45°, 60°, and 90° flexion among all subjects (mean 10.8° vs 6.8°, 12.5° vs 9.4°, 12.8° vs 10.0°, and 11.3° vs 9.5°; p < 0.0001, < 0.0001, < 0.0001, and 0.0008, respectively). The post‐operative total rotational laxity significantly decreased, compared with pre‐operative levels, at 30° and 45° flexion among all subjects (mean 20.4° vs 17.9°, and 23.1° vs 21.1°; p = 0.002 and 0.04, respectively). The post‐operative total rotational laxity was significantly smaller in asymmetrically designed total knee arthroplasty than in symmetrically designed total knee arthroplasty at 30°, 45°, and 60° flexion (mean 19.3° vs 15.8°, 22.8° vs 18.7°, and 24.4° vs 20.8°; p = 0.03, 0.03, and 0.02, respectively), whereas no significant difference was observed at 90° flexion. Conclusion Compared to symmetrical surface design, asymmetrical surface design resulted in lower rotational laxity at the midflexion range in cruciate‐retaining total knee arthroplasty. Level of evidence III.